Tuban Regency KPU Social Media Management (Instagram) in the 2020 Pilkada Stages in the Era of the Covid-19 Pandemic - Anis Miswoni; Pawito; Ign. Agung Satyawan (Jurnal Sosial, Politik dan Budaya (SOSPOLBUD), 2023)
The Tuban Regency Election Commission's social media has a low engagement rate. Instagram @kpu_tuban3523's engagement rate is 0.41% with an average number of interactions of 9 likes and 0 comments. The aim of the study was to find out the management of the Tuban Regency KPU Instagram social media in the 2020 Pilkada in the Era of the Covid-19 pandemic. Social media management uses 4 stages of theory. The methodology used is qualitative. Data collection techniques with in-depth interviews and documentation. The findings of this study are that the management of the Tuban Regency KPU's social media is carried out in 4 stages, but several implementation stages of the management carried out by the Tuban Regency KPU are somewhat less than optimal at the optimize, manage, and engage stages, this is based on a lack of Human Resources in managing Regency KPU social media Tuban.